(3GdGfJUGQ Ydi YdeGA GdCeUGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Gdbhd ai cjajI UQa GdRcGI Edi eSJMbjgG s
(3BNQgG (B:s
(3BNQg ef HGH GdML (B: (3hbO fLR YQVfG ef HjGf GdCehQ GdeMXhQI Ydi GdeMQe eeG jJYdb HGdEMQGe hGdMQe hGddg Gdehab ddUhGH s
(3bdjdI GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis